Monkeypox: the resurgence of forgotten things - Sun Bean Kim; Jaehun Jung; Kyong Ran Peck (Epidemiology and Health, 2022)
Monkeypox, a rare zoonotic disease, is primarily prevalent in Central and Western Africa. However, monkeypox is emerging as a worldwide concern due to the 2022 monkeypox outbreak, which is the first instance of widespread community transmission outside Africa. Monkeypox is caused by the monkeypox virus, which belongs to the genus Orthopoxvirus and presents as a vesicular-pustular disease that may be preceded by fever, malaise, and other constitutional symptoms. If present, lymphadenopathy may distinguish it from chickenpox or smallpox. However, contrary to previous manifestations, most monkeypox patients presented with atypical features during the 2022 outbreak. Monkeypox is usually a self-limiting disease with symptoms lasting between 2 weeks and 4 weeks and is mainly transmitted when a person comes into contact with an infected animal, person, or fomites contaminated with the virus. Very few treatment options are available for this disease. Tecovirimat has been licensed in some countries for the treatment of smallpox and monkeypox infections. Two other medications, cidofovir and brincidofovir, have been found to be effective against poxviruses in in vitro and animal studies, but data on human cases of monkeypox are limited. Although Imvamune (JYNNEOS), a vaccine against monkeypox, is authorized in the United States, there are currently no established routine vaccination programs. Current preventive strategies focus on the detection of probable cases and containment of the outbreak through the implementation of selected ring vaccination programs. Fundamental principles to prevent the spread of monkeypox, including maintaining personal hygiene and avoiding close contact with symptomatic patients, are of paramount importance.